Profile of Prescribing Practice at A Referral Hospital in Indonesia Using Who Drug Use Indicators: Profile of Prescribing Practice at A Referral Hospital in Indonesia Using Who Drug Use Indicators - Dyah Utami, Milati; Kristina, Susi Ari; Zulkarnain, Abdul Karim (Iranian Journal of Pharmaceutical Sciences, 2019)
To promote rational drug use in developing countries, assessment of drug use patterns using the WHO drug use indicators is becoming standard in documenting rational prescribing. The aim of this study was to assess the drug prescription patterns at the Outpatient Pharmacy Department of Sleman District Hospital, using the WHO drug use core indicators. A descriptive cross-sectional survey was conducted. The sample was selected using systematic random sampling of 700 patient encounters were reviewed retrospectively for a one year period from January 2017 to December 2017. Data were collected using an investigator-administered data collection form.The main outcome measured is patterns of drug use measured using WHO core drug use indicators. The data obtained showed that, out of total drugs prescribed (2215), the average number of drugs prescribed per encounter or mean was 3.16 (SD 0.89) with a range between 1 and 4. The percentage of encounters in which an antibiotic prescribed was 15.75%. The Percentage of drugs prescribed by generic name and from a national drug list was 95.66% and 97.78, respectively. The most commonly prescribed forms of antibiotics were amoxicillin 10.74%. The number of drug prescribed shows deviation from the standard recommended by WHO. Drug use evaluation should be done for unnecessary medication. Developing guidelines in place for the optimal and responsible use of antibiotics which could be monitored and feedback provided on a regular basis to prescribers.